How Leaders' Diversity Beliefs Alter the Impact of Faultlines on Team Functioning. (April 2016) - Schölmerich, Franziska; Schermuly, Carsten C.; Deller, Jürgen
Teams with strong faultlines often do not achieve their full potential because their functioning is impaired. We argue that strong diversity beliefs held by team leaders mitigate the negative impact of socio-demographic and experience-based faultlines on team functioning. In a heterogeneous multisource field sample of 217 employees nested in 44 teams and their leaders, we tested our assumptions. Results of a path-analytic model showed that socio-demographic faultlines were negatively related to perceived cohesion and positively related to perceived loafing. The impact of socio-demographic faultlines on team functioning was less detrimental when leaders held strong diversity beliefs. Against our expectations, we found no support for an impact of experience-based faultlines on perceived cohesion or a moderating role of leaders' diversity beliefs in this context. Potential explanations for these results and implications for organizations and team leaders are discussed.